MEDIATOR OF BHABINKAMTIBMAS MULYOSARI VILLAGE, WEST METRO SUBDISTRICT, METRO CITY IN RESOLVING HOUSEHOLD PROBLEMS - Rahman, Ricky; Bakr, Omaima Abou; Asnawi, Habib Shulton; Mukhlishin, Ahmad; Muslih, M; Hidayat, Sarif (Universitas Islam Negeri Raden Intan Lampung, 2022)
This article analyzes the role of Bhabinkamtibmas in making problem solving efforts by prioritizing mediation. The purpose of writing this article is the problem solving techniques of the Habibinkamtibmas in mediating married couples who experience domestic conflicts. In addition, to reveal the obstacles faced when mediating, because when making efforts to assist there are challenges from the parties that are difficult to make peace. This type of research is fielresearch, which is a type of field research, conducted in Mulyosari Village, West Metro Subdistrict, Metro City. The fielresearch was analyzed qualitatively. This research approach was analyzed using a case study approach. The result of the research is the problem solving of the Habibinkamtibmas in mediating domestic problems taken by Aibda Ali Iqbal by taking several steps, namely dissecting the siting of the case that occurred then making observations and then implementing the best solution for the parties, the result of mediation is that both parties take the peaceful path. Meanwhile, the obstacle in conducting mediation is the unanimous determination of the married couple to divorce. In addition, the litigants feel reluctant to reconcile, due to the trauma factor of the events that occurred in their household. If peaceful efforts reach a dead end, then Bhabinkamtibmas' efforts are to take repressive measures both criminally and civilly.Keywords: Problem Solving, Bhabinkamtibmas, Media, Household Problems